Pendampingan Keluarga Sebagai Caregiver Dalam Merawat Pasien Stroke Di Rumah Sakit Mardi Rahayu Kudus - Sri Hindriyastuti; Gardha Rias Arsy; Emma Setyo Wulan; Wahyu Yusianto (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Stroke is a major health problem for modern society today. According to WHO (World Health Organization) in 2016, 51% of stroke deaths worldwide were caused by high blood pressure. Based on data on the top 10 most common diseases in Indonesia in 2018, the prevalence of stroke cases in Indonesia based on health worker diagnosis was 10.9 per mille. Various problems that stroke patients may experience include paralysis, weakness, balance disorders, speech disorders, etc. so that these patients need help in meeting their daily needs. The family as a caregiver has a major role in providing primary support to individuals with stroke and is the first person to respond to changes in the patient's status during the course of the disease. The aim of this community service program is to maximize family assistance as caregivers in caring for stroke patients. The obstacles experienced by caregivers are financial and time problems in accompanying stroke families at Mardi Rahayu Kudus Hospital. Based on the results of interviews that have been conducted, almost all the feelings of families as caregivers in caring for stroke patients are sad, almost all participants answered that the service at Mardi Rahayu Hospital is good and fast, almost all participants' hopes for their husbands are that they can recover quickly, almost all The obstacles experienced by caregivers are financial and time problems. Therefore, assistance and providing motivation to families as caregivers for stroke patients is very important.